The Effect of Job Demands on Journalist Performance in Pikiran Rakyat Newspaper - Agustiani, Rini Ria; Kusmayadi, Ika Merdekawati; Karlinah, Siti (Jurnal Kajian Jurnalisme, 2022)
Journalists are expected to be responsible for fulfilling the public interest in information as well as the demands of media companies. Excessive jobs could have positive and negative impacts on journalists, affecting the increase and decrease of journalists' performance. The job demands can demonstrate the performance or achievements of journalists; the higher the journalists can manage their time well; the journalist performance will increase. This study aims to confirm the sub-dimensional pictures of the variables of job demands and performance of journalists and whether job demands significantly affect the performance of journalists. The method used in this research is quantitative with descriptive analysis and verification. Analytical techniques are used to validate tests, reliability, normality, autocorrelation, and heterodedensity. The hypotheses test uses a simple regression linear test, signification partial (t statistical test), and determination. As a result, the researchers concluded: 1) The work demands of the Pikiran Rakyat Newspaper Journalists did not stress the journalists, and the workload and the work environment were considered good. The demands of work also do not affect the performance of journalists, so the quality of writing, quantity, timeliness, effectiveness, and independence are classified as good. 2) There is a significant positive effect of about 50.7% between the influence of Job Demands on the Performance of Journalists in the Pikiran Rakyat Newspaper. This means that the demands of work do not affect nor make the performance of journalists decrease. However, intrinsic and extrinsic factors can affect the decline of journalists' performance.